q-Derivatives of Multivariable q-Hypergeometric Function with Respect to Their Parameters - Bytev, V. V.; Zhang, P. (Physics of particles and nuclei letters, 2021)
We consider the q-derivatives of the Srivastava and Daoust basic multivariable hypergeometric function with respect to the parameters. This function embodies a entire number of various q-hypergeometric series of one and several variables. Explicit equations are given for general case of summation indexes with positive real coefficients. As an example derivatives of q-analog of non-confluent Horn type hypergeometric function is presented.